Possibilities to form a modern reserve of supporting of a frequency in integrated power systems based on storage batteries for automatic adjustment of frequency and power - Zgurovets; Kulyk М.M. (General Energy Institute of the National Academy of Sciences of Ukraine, 2022)
The paper considers the question creation of an effective system of adjustment of frequency and power using modern energy storage systems based on high-capacity accumulator batteries. Within the framework of the research, different types of frequency and power regulators were considered. The authors proposed an approach to the implementation of the adjustment system with the help of battery energy storage. There were performed comparative calculations of different adjustment systems and was demonstrated the advantage of the suggested approach. The research was performed by numerical simulation of the automatic system of adjustment of frequency and power with emergency imbalance. The efficiency of regulation was determined by the analysis of accepted indicators of regulation quality, namely, the maximum frequency deviation and the duration of the transient process. It was found that the use of the high-speed battery energy storage units in the automatic adjustment system of frequency and power demonstrates the best indicators of frequency stabilization, which satisfy the normative requirements established in the power system. The conducted analysis of the energy and economic indicators has shown the absolute advantage of using battery energy storage systems in both technological and economical terms over other variants of regulators.